2013
DOI: 10.1007/s10072-013-1384-y
|View full text |Cite
|
Sign up to set email alerts
|

Basilar-type migraine patients responsive to lamotrigine: a 5-year follow-up

Abstract: Five years ago we reported the case of three patients affected by basilar-type migraine (BM) responsive to lamotrigine. At that time, proven treatment options for BM are rather limited and lamotrigine has been tested in BM patients because it was a widely tested treatment for migraine with aura. That positive 1-year experience leaded us to suggest that lamotrigine could be a preventive therapeutic option for BM patients, with and without menstruation association. We now report the five-year follow-up of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Consequently, lamotrigine may primarily reduce vestibular symptoms but headache only to a less extent [ 83 ]. Lamotrigine was also reported useful in three patients with basilar-type migraine over 5 years [ 84 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Consequently, lamotrigine may primarily reduce vestibular symptoms but headache only to a less extent [ 83 ]. Lamotrigine was also reported useful in three patients with basilar-type migraine over 5 years [ 84 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The sample included particularly patients who suffered from repeated auras without headache (n = 6), migraine with aphasia during their aura (n = 8), migraine with prolonged aura (>60 minutes, n = 7), basilar‐type migraine (n = 6), or hemiplegic migraine (n = 2). In line, Cologno et al reported in 3 patients having repeated basilar‐type migraine who were treated by LTG at 100 mg/day, a total disappearance of MA attacks over 5 years . The benefit of LTG was also reported in 3 cases of hemiplegic migraine belonging to a family diagnosed with FHM of type 2 and 2 patients with FHM of type 1 .…”
Section: Accumulating Evidence Suggests That Lamotrigine May Reduce Tmentioning
confidence: 61%
“…Therefore, lamotrigine appears to mainly act on vestibular symptoms and only to a lesser extent on headaches ( 41 ). Lamotrigine was also effective in three patients with basilar-type migraine over five years ( 42 ).…”
Section: Methodsmentioning
confidence: 99%